A case of IgG4‐positive plasma cell‐rich tubulointerstitial nephritis in a kidney allograft mimicking IgG4‐related kidney disease. (June 2014) - Nishikawa, Kouhei; Takeda, Asami; Masui, Satoru; Kanda, Hideki; Yamada, Yasushi; Arima, Kiminobu; Morozumi, Kunio; Sugimura, Yoshiki
Abstract: A 51‐year‐old woman received an ABO blood type‐incompatible renal transplant. She was administered rituximab and basiliximab and underwent plasma exchanges for induction therapy, followed by administration of tacrolimus, mycophenolate mofetil and methylprednisolone as maintenance immunosupression therapy. A planned renal biopsy 2 years after transplantation revealed infiltration of plasma cells in the renal interstitium, although there was no 'storiform' fibrosis surrounding these cells. There were also no findings of rejection, BK virus nephropathy, or atypical plasma cells. Immunohistochemical stainings showed a large number of IgG4‐positive plasma cells, most of which expressed kappa‐type light chains. A CT scan showed a mass at the renal hilum. The serum IgG4 level was high. Based on these findings, the patient was suspected of having IgG4‐related kidney disease. Nine months after the biopsy, her serum creatinine level increase to 1.56 mg/dL and the dose of methylprednisolone was therefore increased to 16 mg/day. Three months after this increase in steroid, a CT scan showed the hilum mass had disappeared. A follow‐up biopsy 5 months later showed that infiltration of plasma cells in the renal interstitium had decreased markedly, although focal and segmental severely fibrotic lesions with IgG4‐positive plasma cells were observed. Serum IgG4 levels decreased immediately after the increase in steroid dose and remained <100 mg/dL despite a reduction in methylprednisolone to 6 mg/day. Serum creatinine levels also remained stable at around 1.6 mg/dL. To our knowledge, this is the first report of IgG4‐positive plasma cell‐rich tubulointerstitial nephritis mimicking IgG4‐related kidney disease after kidney transplantation.